Optimization of simvastatin transdermal patch for hyperlipidemia treatment in rat model - Neetu; Anubhav Anand; Dharamveer Panjwani (SpringerOpen, 2024)
Abstract Objective Biopharmaceutics Classification System says that simvastatin (SMV) is a Class II drug with low bioavailability (5%). This is because it dissolves slowly and is broken down a lot in the first pass. Simvastatin transdermal patches were produced as part of this study's aim to treat hyperlipidemia. The Box-Behnken design (three-factor, three-level) was selected for optimization of patches. Methodology The optimization design involved 15 runs with independent factors hydroxypropyl methylcellulose K100, Eudragit L100, and polyethylene glycol 400 percentage, and dependent factors including folding endurance and in-vitro drug release. Results The results showed that the concentration of hydroxypropyl methylcellulose K-100 positively impacted the patch's folding endurance. The fact that factor C was the only scenario where the p-value was less than 0.05 and the coefficient value was higher in the in vitro drug release model means that it has a greater influence on the release of medicines. The patches were also evaluated for drug content, swelling, moisture uptake, moisture content, etc. The optimized patch shows an in vitro drug release of 55.3% in up to 24 h. In vivo antihyperlipidemic activity was evaluated in albino Wistar rats. In the standard treatment (simvastatin oral) groups, there is a decrease in cholesterol (132.76 ± 0.35) and triglyceride level (139.80 ± 76) whereas in the test formulation group or test group, there is also a decrease in cholesterol (169.65 ± 0.21 mg/dL) and triglyceride level (151.20 ± 31 mg/dL) level. Conclusion Based on in-vitro and in-vivo results it can be concluded that simvastatin patches can be an alternative to traditional therapy.